Sirtuin 1 Regulates SREBP-1c Expression in a LXR-Dependent Manner in Skeletal Muscle - Defour, Aurélia; Dessalle, Kevin; Castro Perez, Andréa; Poyot, Thomas; Castells, Josiane; Gallot, Yann Simon; Durand, Christine; Euthine, Vanessa; Gu, Yansong; Béchet, Daniel; Peinnequin, André; Lefai, Etienne; et al. (PLOS ONE, 2012)
Sirtuin 1 (SIRT1), a NAD+-dependent protein deacetylase, has emerged as a main determinant of whole body homeostasis in mammals by regulating a large spectrum of transcriptional regulators in metabolically relevant tissue such as liver, adipose tissue and skeletal muscle. Sterol regulatory element binding protein (SREBP)-1c is a transcription factor that controls the expression of genes related to fatty acid and triglyceride synthesis in tissues with high lipid synthesis rates such as adipose tissue and liver. Previous studies indicate that SIRT1 can regulate the expression and function of SREBP-1c in liver. In the present study, we determined whether SIRT1 regulates SREBP-1c expression in skeletal muscle. SREBP-1c mRNA and protein levels were decreased in the gastrocnemius muscle of mice harboring deletion of the catalytic domain of SIRT1 (SIRT1Δex4/Δex4 mice). By contrast, adenoviral expression of SIRT1 in human myotubes increased SREBP-1c mRNA and protein levels. Importantly, SREBP-1c promoter transactivation, which was significantly increased in response to SIRT1 overexpression by gene electrotransfer in skeletal muscle, was completely abolished when liver X receptor (LXR) response elements were deleted. Finally, our in vivo data from SIRT1Δex4/Δex4 mice and in vitro data from human myotubes overexpressing SIRT1 show that SIRT1 regulates LXR acetylation in skeletal muscle cells. This suggests a possible mechanism by which the regulation of SREBP-1c gene expression by SIRT1 may require the deacetylation of LXR transcription factors.